- UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV MATERI MEMBEDAKAN FAKTA DAN OPINI DENGAN MODEL COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA PUZZLE DI SDN GLONGGONG 01 - Afifah Salsabila; Putri, Dewi Kartika; Firsa Aprilia Anggraini; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted to improve student learning outcomes through the implementation of the Team Games Tournament (TGT) Cooperative Learning Model Assisted by Puzzle Media. This research was motivated by the low learning achievement of students caused by the lack of student interest in Indonesian language lessons because they were too focused on the content of the material without learning media. The classroom action approach used in this research was carried out in one cycle including the planning, implementation, observation, and reflection stages. The subjects of this research were 19 fourth grade students of SDN Glonggong 01 Madiun. The data analysis technique used was quantitative descriptive. The data collection instrument in this research was a learning outcome test. The results showed that in the pre-cycle stage, the level of student learning completeness only reached 16%, indicating that most students did not understand the material well. After the implementation of the Teams Games Tournament (TGT) Cooperative Learning Model assisted by puzzle media in cycle I, there was a very significant increase with the percentage completeness reaching 100%. This shows an increase of 84% from the initial pre-cycle conditions. This improvement proves that the TGT model assisted by puzzle media is able to facilitate understanding of the material in a fun way, encourage group cooperation, and foster students' enthusiasm for learning. All students have achieved the Minimum Completion Criteria (KKM) in cycle I.